Design of Programmable High-Cost-Performance Gantry-Type Loading and Unloading Manipulator - Zhou, Lijie; Cai, Chunlin; Hao, Ruilin (International Journal of Mechanical and Electrical Engineering, 2026)
To meet the demand for low-cost, highly reliable, and easily programmable loading and unloading equipment in automated CNC machining production lines, this paper designs a three-axis gantry-type loading and unloading manipulator. The whole machine adopts a gantry frame and a Cartesian coordinate structure, with stepper motors and synchronous belts as the transmission scheme, and is equipped with a pneumatic clamping end effector to realize the automatic transfer of workpieces between machine tools and silos. The control system is built with a PLC, stepper motor drivers and a touch screen, supporting touch screen programming, point-to-point motion, signal input and output control, delay control and other functions. The human-machine interaction system adopts a touch screen for visual operation, reducing the threshold of debugging and use. Through lightweight structural design, modular component design and simplified programming design, on the premise of ensuring a repeated positioning accuracy of ±0.1 mm and stable and reliable operation, the overall cost and deployment cycle of the machine are significantly reduced. Prototype tests show that the manipulator meets the requirements of flexible processing for small and medium batch production and has high engineering application value.